A service evaluation of the therapy assessments used for preoperative wrist surgery assessments within a single National Health Service Trust. (December 2015) - Donnison, Ella; Woodbridge, Sarah
Introduction: Chronic wrist joint pain is complex and often managed surgically. Where pain predominates, but function and movement are good, conservative or less invasive procedures may be preferable, such as denervation. To aid surgical selection denervation effectiveness can be predicted by a wrist assessment including nerve blocks. While much literature exists for denervation surgery no research to date has explored nerve blocks from a therapy assessment perspective. The purpose of this service evaluation was to establish current assessment practice, provide an important starting point to discuss why assessments may be selected and aid understanding of the assessment service provided. Methods: A service evaluation was undertaken. The assessments selected by three therapists for cases referred for a preoperative wrist assessment were recorded and analysed. Results: Fourteen participants were recruited during a five-month period. The mean age was 57.43 years (range 21–79). Two assessments were terminated to address conservative management. Of the remaining 12 participants, assessments included range of motion, cumulative and resting pain 100% (n = 12), grip and pinch strength 92% (n = 11), function 17% (n = 2) and Baltimore Therapeutic Equipment static and dynamic movements 92% (n = 11). Conclusion: This time-limited evaluation provides insight into the varied assessments used, by therapists within a single NHS Trust, to simulate activity and/or wrist structures under stress. The assessment is a global patient-centred process which aids identification of strategies for conservative and surgical procedures including denervation surgery. Despite the small sample, trends were noted in the practices of experienced hand therapists.